Patterns of Prescribed Drugs and Knowledge of Use of Drug Delivery Devices among Adult Bronchial Asthma Patients in a Tertiary Hospital in Bangladesh (Community Based Medical Journal, 2025)
The prevalence of asthma has grown steadily over the decades in developing countries like Bangladesh. A cross-sectional, observational study was carried out in the Department of Pharmacology & Therapeutics in collaboration with the Department of Respiratory Medicine and Internal Medicine of Mymensingh Medical College Hospital, Mymensingh, Bangladesh, from July 2017 to June 2018, to explore drug prescription pattern and knowledge of use of drug delivery devices among bronchial asthma patients. A total of 160 adult patients (≥18 years) were selected non-randomly for this study. A total of 225 metered dose inhaler (MDI) were prescribed, which constituted the most common mode of administration of drugs to the asthmatic patients (48.07%), followed by oral tablet 223(47.66%) and accuhaler inhaler 20(4.27%). Out of 160 patients, 139 patients were treated with inhalation therapy. Among 139 patients, 46(33.09%) patients received an MDI with spacer; all of them knew how to use the device properly. 73(52.52%) patients received only MDI; among them, only 30(41%) patients could use the device properly. 20(14.39%) patients received accuhaler and all of them could use the device properly. CBMJ 2025 January: Vol. 14 No. 01 P: 115-117